(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The main goal of the study is to reveal the essence and specifics of international conflicts in the context of globalization. In accordance with this goal, the following tasks are being carried out in the following stages: - to carry out a system analysis of global trends that affect to specifics of contemporary international conflicts; - show the interdisciplinary nature of global problems and identify the main directions of global studies;- to identify the essence of the main global problems and their impact on international conflicts; - to disclose the substantive basis of international conflicts, to show the interrelation of the main characteristics of the globalization process with the political features of modern world development. Theoretical and methodological basis of the research are the works of domestic and foreign specialists dealing with the problems of globalistics and conflictology. Important theoretical basis of the work are the works of modern political scientists, international experts, jurists, sociologists, and others.The initial methodological principles of the problem analysis are: the principle of historicism, the principle of an integrated approach to solving the problem. Theoretical principles are implemented by using the method of analogy and extrapolation, systematization and interdisciplinary approach.The scientific and practical significance of the research is determined by the fact that its results can be used in the development of courses in political science, international relations, conflictology, sociology and other humanitarian disciplines, they can be useful in the activities of the media, foreign and domestic policy departments and other state structures In the analysis of conflicts in society and the ability to make managerial decisions in conflict situations. Key words: globalization, international conflict, domestic and foreign policy, modern world development, international relations.